2009
DOI: 10.1159/000222092
|View full text |Cite
|
Sign up to set email alerts
|

Combined Memory and Executive Function Tests Can Screen Mild Cognitive Impairment and Converters to Dementia in a Community: The Osaki-Tajiri Project

Abstract: Background: The borderline condition between health and dementia, defined as Clinical Dementia Rating (CDR) 0.5, should be detected for the possible prediction of dementia. Since the CDR requires information from collateral sources, it is difficult to rate people living alone. The aim is to develop a set of tests without collateral information for detecting CDR 0.5 and converters to dementia. Methods: 625 participants were selected from the community; 412 were CDR 0 (healthy), 168 were CDR 0.5 (defined here as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…In a study of male sailors, Hansen et al found that 5-minute supine HF HRV was positively associated with cognitive test scores that used executive function, but not with tests that did not use executive function [50]. Poor working memory and executive function may portend increased risk of later dementia [51], which several studies have also found to be associated with HRV [11, 15, 52, 53]. Our study expands upon the findings of previous smaller studies by finding an association between verbal learning and memory with more prognostic, long-term HRV measures that are independent of cardiovascular comorbidities, depression, familial factors, and genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of male sailors, Hansen et al found that 5-minute supine HF HRV was positively associated with cognitive test scores that used executive function, but not with tests that did not use executive function [50]. Poor working memory and executive function may portend increased risk of later dementia [51], which several studies have also found to be associated with HRV [11, 15, 52, 53]. Our study expands upon the findings of previous smaller studies by finding an association between verbal learning and memory with more prognostic, long-term HRV measures that are independent of cardiovascular comorbidities, depression, familial factors, and genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…41 This model exhibited high sensitivity (93%) and low specificity (66%) for the prediction of 5 year dementia in individuals aged ≥65 years (AUC 0.88), 41 but did not outperform the mmse in this sample (sensitivity 81%, specificity 65% and AUC 0.81). moreover, the predictive ability of the four-test model was not improved with adjustment of the limits on age (that is, to restrict the sample to individuals aged 70-79 years) or the test outcome (to AD or mixed AD and vascular dementia, rather than dementia), or reduction of the model to include only tests of memory.…”
Section: Negative Predictive Value (Npv)mentioning
confidence: 94%
“…34 Dementia risk models have mainly drawn on data from neuropsychological testing and sociodemographic variables, including age, sex and education. These models can be broadly divided into the following categories: cognitive profiles (descriptions of the various cognitive tests used in such models are outlined in Table 1); [35][36][37][38][39][40][41][42][43][44] health and vascular risk indices; 45,46 multifactorial models typically combining demographic and neuro psychological measures with health or genetic variables; 34,47,48 multi stage screening approaches; 49 and multi-dementia subtype preclinical groupings. 50 Details of the methods and design of each dementia risk model study are presented in supplementary Table 2 online.…”
Section: Mild Cognitive Impairment Criteriamentioning
confidence: 99%
“…A study of 168 community-based elderly persons showed that the total MMSE score predicts the risk of conversion to dementia within 5 years among people with MCI, with a sensitivity of 82% but a specificity of only 62% [17]. In contrast, the MMSE suffers from low sensitivity to dementia conversion in studies conducted in clinical samples.…”
Section: Introductionmentioning
confidence: 99%